The Role of Autophagy in Manganese-Induced Neurotoxicity - Yan, Dong-Ying; Xu, Bin (Frontiers in Neuroscience, 2020)
Manganese (Mn), an essential micronutrient, acts as cofactor for multiple enzymes. Epidemiological investigations have shown that an excessive level of Mn is an important environmental factor involved in neurotoxicity. Frequent pollution of air and water by Mn is a serious threat to the health of the population. Overexposure to Mn is particularly detrimental to the central nervous system, leading to symptoms similar to several neurological disorders. Many different mechanisms have been implicated in Mn-induced neurotoxicity, including oxidative/nitrosative stress, toxic protein aggregation, endoplasmic reticulum (ER) stress, mitochondrial dysfunction, dysregulation of autophagy, and the apoptotic cascade, which together promote the progressive neurodegeneration of nerve cells. As a compensatory regulatory mechanism, autophagy plays dual roles in various biological activities under conditions of pathological stress. Dysregulation of autophagy has been found to be involved in the development of neurodegenerative disorders, with recent emerging evidence indicating a strong, complex relationship between autophagy and Mn-induced neurotoxicity. This review discusses the connection between autophagy and Mn-induced neurotoxicity, especially in relation to alpha-synuclein oligomerization, ER stress, and aberrated protein S-nitrosylation, which provide new insights for deeply exploring the precise mechanisms of Mn-induced neurotoxicity.